2007
DOI: 10.1080/10826070701588984
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Application of High Speed Countercurrent Chromatography Coupled with Direct Injection of the Powders of a Raw Material without any Preparation, for Isolation and Separation of Four Alkaloids with High Recoveries from Coptis chinensis Franch

Abstract: Generally, before a successful high speed countercurrent chromatography (HSCCC) separation, crude samples were extracted from medicinal plants by aqueous ethanol or other organic solvents, and then the extracts were cleaned up by liquid-liquid extraction or column chromatography to produce the suitable samples for further purification, which were hostile for our environment and natural resource reserve because more time and solvent were consumed, and there was sample loss with a low recovery. In view of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The calculations revealed that the major component of the extract among the tested isoquinoline alkaloids was berberine ( 13 ) with the content of 6.21 ± 0.23%, followed by palmatine ( 12 ) (1.62 ± 0.031%), epiberberine ( 9 ) (1.53 ±0.018), jatrorrhizine ( 10 ) (0.621 ±0.019%) and coptisine ( 11 ) (0.495 ± 0.0052%). The quantity calculated for berberine ( 13 ) and palmatine ( 12 ) resembled the one reported by Peng and collaborators [ 32 ], who determined their quantity as 6.88 and 1.46%, respectively. The concentration of the remaining compounds was lower in the herein tested sample, as the other authors reported 1.02% of 10 and 1.37% of 11 in their sample.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The calculations revealed that the major component of the extract among the tested isoquinoline alkaloids was berberine ( 13 ) with the content of 6.21 ± 0.23%, followed by palmatine ( 12 ) (1.62 ± 0.031%), epiberberine ( 9 ) (1.53 ±0.018), jatrorrhizine ( 10 ) (0.621 ±0.019%) and coptisine ( 11 ) (0.495 ± 0.0052%). The quantity calculated for berberine ( 13 ) and palmatine ( 12 ) resembled the one reported by Peng and collaborators [ 32 ], who determined their quantity as 6.88 and 1.46%, respectively. The concentration of the remaining compounds was lower in the herein tested sample, as the other authors reported 1.02% of 10 and 1.37% of 11 in their sample.…”
Section: Resultssupporting
confidence: 82%
“…That is why the authors decided on the addition of TEA to the upper phase (as described by Sun and co-investigators [ 25 ]) and to conduct the separation in the pH-zone refining mode. A similar solvent system selectiveness in the recovery of isoquinoline alkaloids from Coptis chinensis to the herein proposed method was described by Peng and collaborators [ 32 ]. These researchers also obtained berberine ( 13 ), palmatine ( 12 ), jatrorrhizine ( 10 ) and coptisine ( 11 ) on an HSCCC chromatograph within 240 min, applying the rotation speed of 850 rpm and the flow rate of 2 mL/min and using a biphasic solvent system composed of n-hexane: ethyl acetate: methanol: 1% acetic acid (1:1:1:1 v/v/v/v ).…”
Section: Resultsmentioning
confidence: 98%
“…Many papers have been reported to separate alkaloids from this plant by HSCCC [22,23]. The solvent system composed of chloroform-methanol-water is considered to be one of the classical solvent systems in alkaloids purification, but the ratios between the solvents were not invariable.…”
Section: Optimization Of Hsccc Conditionsmentioning
confidence: 99%
“…Peng et al [23] also separated four alkaloids with high recoveries from C. chinensis by HSCCC with direct injection the powders of a raw materials without any preparation. It was not difficult to find that only four alkaloids were purified, and the purities of some products were not high enough.…”
Section: Introductionmentioning
confidence: 99%
“…Fast centrifugal partition chromatography (FCPC) is a type of liquid-liquid chromatography that has shown to be very versatile and fast for the isolation and separation of natural products 26 . The reviews by Leitão et al 27 and Fang et al 28 indicate that this technique is well suitable for BIA isolation too, as, for example, evidenced by the isolation of coptisine and berberine from Coptis chinensis root by classical biphasic 29 , 30 , triphasic 31 , and pH zone refining countercurrent chromatography 32 , 33 . However, for C. majus , no respective method has been published.…”
Section: Introductionmentioning
confidence: 99%